Comparison of temporary interruption with continuation of direct oral anticoagulants for low bleeding risk procedures. Issue 203 (July 2021) - Sheikh, Muhammad Adil; Kong, Xiaowen; Haymart, Brian; Kaatz, Scott; Krol, Gregory; Kozlowski, Jay; Dahu, Musa; Ali, Mona; Almany, Steven; Alexandris-Souphis, Tina; Kline-Rogers, Eva; Froehlich, James B.; et al.
Abstract: Introduction: Limited data is available on the rates of bleeding and thromboembolic events for patients undergoing low bleeding risk procedures while taking direct oral anticoagulants (DOAC). Methods: Adults taking DOAC in the Michigan Anticoagulation Quality Improvement Initiative (MAQI 2 ) database who underwent a low bleeding risk procedure between May 2015 and Sep 2019 were included. Thirty-day bleeding (of any severity), thromboembolic events, and death were compared between DOAC temporarily interrupted and continued uninterrupted groups. Adverse event rates were compared using an inverse probability weighting propensity score. Results: There were 820 patients who underwent 1412 low risk procedures. DOAC therapy was temporarily interrupted in 371 (45.2%) patients (601 [42.6%] procedures) and continued uninterrupted in 449 (54.8%) patients (811 [57.4%] procedures). DOAC patients with temporary interruptions were more likely to have diabetes, prior stroke or TIA, prior bleeding, higher CHA2DS2-VASc, and higher modified HAS-BLED scores. DOAC interruption was common for gastrointestinal endoscopy, electrophysiology device implantation, and cardiac catheterization while it was less common for cardioversion, dermatologic procedures, and subcutaneous injection. After propensity score adjustment, bleeding risk was lower in the DOAC temporary interruption group (OR 0.62, 95% CI 0.41–0.95) as compared to the group with continuous DOAC use. Rates of thromboembolic events and death did not differ significantly between the two groups. Conclusions: DOAC-treated patients undergoing low bleeding risk procedures may experience lower rates of bleeding when DOAC is temporarily interrupted. Prospective studies focused on low bleeding risk procedures are needed to identify the safety DOAC management strategy. Highlights: Limited data available on bleeding and thromboembolic risk for low bleeding risk procedures and direct oral anticoagulants (DOAC) DOAC patients with low bleeding risk procedures were more likely to have diabetes, prior stroke, prior bleeding, and higher stroke/bleed risk scores Bleeding risk was lower in the DOAC temporary interruption group as compared to the group with continuous DOAC use peri-procedurally Risk of thromboembolic events and death did not differ significantly between the two groups